Analisis Rasionalitas Penggunaan Antipsikotik pada Pasien Skizofrenia di Instalasi Rawat Inap RSJD Atma Husada Mahakam Samarinda Tahun 2016 - Saputri, Rika Paramitha; Sulistyawati, Elina Endang; Untari, Meta Kartika (Universitas Muhammadiyah Surakarta, 2018)
Schizophrenia is a chronic heterogeneous syndrome characterized by irregular mindset, delusion, hallucination, improper behavioral changes, and psychosocial dysfunction. The purpose of this research was to know the pattern of antipsychotic use and rationality of antipsychotic use in schizophrenia patient at Inpatient Installation of Atma Husada Mahakam Psychiatric Hospital Samarinda in 2016 based on right indication, right drug selection, right patient, and right dose. The study was use descriptive non-experimental method with retrospective data collection from medical record of patients with purposive sampling technique. The samples used was 94 patients who received antipsychotic with age range 17-55 years and had a complete medical history. The data obtained were analyzed according to Guideline Texas Medication Algorithm Project Procedural Manual of Schizophrenia Treatment Algorithms. Based on the results obtained data of single antipsychotic the most widely used was haloperidol as 39 prescriptions (53.42%). The use of the most commonly prescribed combination of two antipsychotic was combination of clozapine-haloperidol as 19 prescriptions (38,00%), while combination of three prescribed antipsychotic was combination of chlorpromazine-risperidone-clozapine and haloperidol-risperidone-clozapine each as 1 prescription (50,00%). The rationale of antipsychotic use obtained percentage of right indication was 100%, right drug selection 95,20%, right patient 100%, and right dose 100%.